Jaundice as an atypical manifestation of the new coronavirus infection. Case report - Irina M. Pichugina; Irina M. Ogoltsova (ZAO "Consilium Medicum", 2022)
In many cases, the clinical presentation of SARS-CoV-2, seeking to the epithelium of the respiratory tract, was typical and affected only the respiratory system, but if we look at the statistics, other clinical findings were also encountered. In particular, the virus can also affect the gastrointestinal tract. There was an outbreak of SARS in 2002, and more than 70% of patients had dyspeptic disorders. In 2012, there was an outbreak of the Middle East respiratory syndrome and a quarter of patients had similar symptoms. And there were cases in which it was dyspepsic phenomena that came to the forefront and respiratory phenomena only afterwards. Already in 2012, this behavior of coronavirus made it difficult to make a correct diagnosis. SARS-CoV (2002), MERS-CoV (2012), and the new SARS-CoV-2 (2019) belong to the genus Betacoronavirus, and the genome sequence of SARS-CoV-2 is similar at 82% to that of severe acute respiratory syndrome coronavirus. The kinship of the viruses should alert physicians and always warn that an atypical clinical picture of the disease is possible, as has been the case in the past. This article describes a clinically interesting patient. Jaundice is the only symptom, a symptom that confuses doctors, because no one could think of a coronavirus infection in this case. The purpose of this article is to show on the example of a patient that it is difficult to diagnose the main diagnosis in case of atypical symptomatology of COVID-19. Therefore, also in cases of liver damage it is necessary to collect the anamnesis qualitatively, to make differential diagnosis not only within the framework of gastroenterology, but also in present conditions suspecting a new coronavirus infection.